Frequency of Coexisting Meningitis in Neonates Admitted with Late-Onset Sepsis in Nursery, MTI DHQ Hospital, Dera Ismail Khan: Meningitis in Neonates - Khan, Ayesha; Burki, Farmanullah; Khan, Imran; Yahya, Alina; Khan, Oushna (Pakistan Journal of Health Sciences, 2025)
Neonatal Late-Onset Sepsis (LOS) is a serious condition that can lead to co-existing meningitis, increasing the risk of long-term complications and mortality. Early diagnosis remains challenging due to non-specific clinical symptoms and limitations in performing Lumbar Punctures (LPs). Objective: To determine the frequency of co-existing meningitis in neonates with LOS and identify clinical and laboratory markers associated with it. Methods: Neonates aged ≥72 hours with signs of LOS were included. Demographic data, clinical symptoms, and laboratory parameters were recorded. A comparative cross-sectional study was conducted in the neonatal nursery of DHQ Hospital, MTI, Dera Ismail Khan. Blood samples were analyzed for C - Reactive Protein (CRP), White Blood Cell (WBC) count, and blood culture, while CSF analysis included WBC count, protein, glucose, and culture. Data were analyzed using SPSS version 25.0, with the Chi-square test used for categorical variables and independent t-tests for continuous variables. A p-value of <0.05 was considered statistically significant. Results: Among 95 neonates with LOS, 53.7% had meningitis. Lethargy (p = 0.024) and previous antibiotic use (p = 0.034) were significantly associated with meningitis, while other clinical signs showed no significant difference. CSF analysis revealed elevated WBC counts in meningitis cases, but CRP and blood WBC were not significantly different. Conclusions: Meningitis was frequent among neonates with LOS, with lethargy and prior antibiotic use as key risk factors. Early identification of these factors may aid in timely diagnosis and intervention. Further multi-center studies are recommended to validate these findings.